2002
DOI: 10.1016/s0165-1765(02)00009-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and output growth uncertainty and their relationship with inflation and output growth

Abstract: Using a bivariate GARCH model of inflation and output growth we find evidence that higher inflation and more inflation uncertainty lead to lower output growth in the Japanese economy. These results support the argument of a price stability objective for the monetary authority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 11 publications
4
60
0
2
Order By: Relevance
“…Finally, several of our results square with the findings of recent studies by Fountas et al (2002), Fountas et al (2004a) and Conrad and Karanasos (2005a). In particular, Fountas et al (2002) employ Japanese data (1961e1999) and a bivariate GARCH model (where inflation is measured by PPI) and find similar results to the PPI results of the present study.…”
Section: Discussion Of Results and Related Recent Literaturesupporting
confidence: 91%
See 3 more Smart Citations
“…Finally, several of our results square with the findings of recent studies by Fountas et al (2002), Fountas et al (2004a) and Conrad and Karanasos (2005a). In particular, Fountas et al (2002) employ Japanese data (1961e1999) and a bivariate GARCH model (where inflation is measured by PPI) and find similar results to the PPI results of the present study.…”
Section: Discussion Of Results and Related Recent Literaturesupporting
confidence: 91%
“…In particular, Fountas et al (2002) employ Japanese data (1961e1999) and a bivariate GARCH model (where inflation is measured by PPI) and find similar results to the PPI results of the present study. The only difference is lack of evidence for the Black hypothesis in Fountas et al (2002).…”
Section: Discussion Of Results and Related Recent Literaturesupporting
confidence: 82%
See 2 more Smart Citations
“…The factor, growth in output is also linked to innovation. However, Fountas et al (2002) found that it is influenced by other factors such as inflation and inflation uncertainty. Therefore, it is not suitable to be used in this study.…”
Section: Theoretical Frameworkmentioning
confidence: 99%